(untitled) (Al-Aasar, 2025)
This research provides an in-depth analytical study of the discursive and theological aspects embedded in the Malfoozat (verbal sayings) of prominent Chishti Sufi saints in the Indian subcontinent, including Hazrat Khwaja Usman Harooni, Hazrat Khwaja Moeenuddin Chishti, Hazrat Baba Fariduddin Ganjshakar, Hazrat Khwaja Nizamuddin Auliya, Hazrat Khwaja Qutbuddin Bakhtiyar Kaki, Hazrat Khwaja Shah Suleman Tunesvi, Hazrat Khwaja Shamsuddin Sialvi, Syed Jahangir Ashraf Samnani, and Pir Mehr Ali Shah. The study emphasizes that these Malfoozat were far more than mere spiritual exhortations or ethical admonitions; they encompassed profound reflections on key Islamic beliefs, theological doctrines, and the articulation of Sunni orthodoxy within the spiritual, social, and historical realities of their time. A central focus of these sayings is the concept of Tawhid (divine unity), which the saints presented not only as a metaphysical principle but also as the practical foundation of a believer’s life. Saints such as Hazrat Khwaja Moeenuddin Chishti and Hazrat Baba Fariduddin Ganjshakar stressed that acknowledgment of God’s oneness must manifest in all aspects of human conduct. Hazrat Khwaja Shah Suleman Tunesvi and Hazrat Khwaja Shamsuddin Sialvi, for instance, elaborated on the attributes of God with a balance between affirming divine qualities as real and avoiding extremes of anthropomorphism or abstraction, following classical Sunni theological traditions while remaining accessible to general audiences. The study also explores the Malfoozat’s treatment of prophethood, faith, and human deeds. Saints such as Pir Mehr Ali Shah emphasized the finality of Prophethood and defended orthodox beliefs against heterodox movements, while Hazrat Khwaja Nizamuddin Auliya and Hazrat Khwaja Qutbuddin Bakhtiyar Kaki highlighted the ethical and practical dimensions of spiritual life alongside doctrinal fidelity. Moreover, the saints addressed complex topics such as the relationship between divine decree (Qadr) and human free will, stressing that while humans are endowed with apparent choice, ultimate control rests with God, thereby reconciling theological doctrine with moral responsibility. Another critical aspect highlighted is the saints’ engagement with heretical or deviant sects, where they combined rational argumentation with spiritual guidance to clarify distinctions between right and wrong for the community. The Malfoozat thus reflect a unique synthesis of rigorous theological discourse, ethical instruction, and spiritual training, maintaining a balance between intellectual depth and practical applicability. In conclusion, the Malfoozat of Hazrat Khwaja Usman Harooni, Hazrat Khwaja Moeenuddin Chishti, Hazrat Baba Fariduddin Ganjshakar, Hazrat Khwaja Nizamuddin Auliya, Hazrat Khwaja Qutbuddin Bakhtiyar Kaki, Hazrat Khwaja Shah Suleman Tunesvi, Hazrat Khwaja Shamsuddin Sialvi, Syed Jahangir Ashraf Samnani, and Pir Mehr Ali Shah serve as a vital repository of Sunni orthodoxy, theological clarity, and spiritual wisdom. They not only guided contemporary audiences but continue to provide insights for modern readers in understanding and defending Islamic beliefs, demonstrating the enduring relevance of Chishti Sufi thought.